Stenting the Superior Petrosal Sinus in a Patient With Symptomatic Superior Semicircular Canal Dehiscence - Ionescu, Eugen C.; Coudert, Aurelie; Reynard, Pierre; Truy, Eric; Thai-Van, Hung; Ltaief-Boudrigua, Aicha; Turjman, Francis (Frontiers in Neurology, 2018)
Patients presenting superior semicircular canal dehiscence (SSCD) can experience symptoms such as conductive hearing loss, pulsatile tinnitus, autophony, and pressure-induced vertigo. Decreased cervical vestibular-evoked myogenic potentials (cVEMPs) thresholds and high-resolution computed tomography (HRCT) of the petrous bone are essential for diagnosis of SSCD syndrome. We report the case of a 43-year-old man suffering from constant right pulsatile tinnitus, intermittent autophony, and unsteadiness induced by physical exercise. An SSCD by the superior petrosal sinus (SPS) was confirmed on the right side by axial HRCT of the temporal bone reformatted in the plane of Pöschl and ipsilateral abnormally low elicited cVEMPs. Treatment options were discussed with the patient since the pulsatile tinnitus progressively became debilitating. Two options were considered: surgery or a new endovascular treatment; the patient chose the latter option. After stenting the right SPS, the intensity of the pulsatile tinnitus dramatically decreased. As there was no complication the patient was discharged at Day 1. The other symptoms improved progressively. By the 60-day follow-up visit the patient only reported a slight tinnitus worsened by physical exercise. Angiographic follow-up at 5 months confirmed the patency of the SPS. Stenting the SPS in patients with SSCD by the SPS appears to be an alternative to the existing surgical treatments. Key words: Third window lesions, Semicircular Canal Dehiscence, Superior Petrosal Sinus, Endovascular Treatment, Pulsatile Tinnitus